The Effect of Discovery Learning vs Conventional and Auditorial vs Kinesthetic Learning Styles on Elementary School Students’ Mathematics Learning Outcomes - Haerudin, Muhamad (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the effect of Discovery Learning strategies and Learning Styles on Student Learning Outcomes at SD Negeri Solear II, Tangerang Regency - Banten. To measure the achievement of objectives by comparing student learning outcomes between Discovery learning and conventional learning strategies and measuring the influence of student learning styles between auditory and conventional on learning outcomes. This research is experimental research. The population of this study were all fifth-grade students at SDN Solear II Tangerang Regency, totaling 74 students consisting of two classes, with details of 37 students in VA class and 37 students in VB class. The sample in this study were 40 students consisting of VB class as the experimental class and VA class as the control class. The instruments in this study were 5 items in the form of essays which were carried out during the pre-test and post-test as well as instruments to measure students' learning styles. The results of the data analysis found that there was a difference in the average value of improving students' mathematics learning outcomes between the control class and the experimental class, where the control class had an average score of 66.75 and was lower than the experimental class which reached 78.75. This means that there is an influence of Discovery Learning strategies and student learning styles on student mathematics learning outcomes.